2016
DOI: 10.1080/02763893.2015.1129383
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Rated Health During the Transition to Retiring Living Among Medicare Managed-Care Recipients

Abstract: Objectives Moving into a retirement community may be precipitated by or bring about changes in health status. We hypothesized that moving into a retirement community would be associated with a decline in self-rated health (SRH), but that health-related factors would mitigate this association. Methods We analyzed data from 58,272 participants in Cohort 3 of the Medicare Health Outcome Survey. Individuals answered questions regarding living status in 2000 and 2002. Those who moved into a retirement community w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Two recent studies support this possibility. Lea et al (2016) analysed data of Cohort 3 of the Medicare Health Outcome Survey, and found that two years after enrolment to the CCRC there was no difference between CCRC residents and non-residents in subjective health. Gaines et al .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies support this possibility. Lea et al (2016) analysed data of Cohort 3 of the Medicare Health Outcome Survey, and found that two years after enrolment to the CCRC there was no difference between CCRC residents and non-residents in subjective health. Gaines et al .…”
Section: Discussionmentioning
confidence: 99%